Bacterial Communities in Polluted Seabed Sediments: A Molecular Biology Assay in Leghorn Harbor - Carolina Chiellini; Renato Iannelli; Franco Verni; Giulio Petroni (The Scientific World Journal)
Seabed sediments of commercial ports are often characterized by high pollution levels. Differences in number and distribution of bacteria in such areas can be related to distribution of pollutants in the port and to sediment conditions. In this study, the bacterial communities of five sites from Leghorn Harbor seabed were characterized, and the main bacterial groups were identified. T-RFLP was used for all samples; two 16S rRNA libraries and in silico digestion of clones were used to identify fingerprint profiles. Library data, phylogenetic analysis, and T-RFLP coupled with in silico digestion of the obtained sequences evidenced the dominance of Proteobacteria and the high percentage of Bacteroidetes in all sites. The approach highlighted similar bacterial communities between samples coming from the five sites, suggesting a modest differentiation among bacterial communities of different harbor seabed sediments and hence the capacity of bacterial communities to adapt to different levels and types of pollution.